Spiritual Values in Multicultural Islamic Education: Gender-Moderated Impact on Student Motivation - Supriyanto Supriyanto; Hamdanah Hamdanah; Mazrur Mazrur; Nola Fibriyani Bte Salman (Jurnal Pemberdayaan Masyarakat, 2026)
This study addresses the growing need to integrate spiritual values into Islamic education within multicultural contexts, recognizing that motivation is a critical determinant of student engagement and achievement. The objective of the research is to analyze the influence of integrating spiritual values in Islamic Religious Education on students’ learning motivation. Employing a quantitative approach, the study adopted a cross-sectional survey design. Data were collected from 479 pesantren students aged 15–18 years, selected through purposive sampling based on academic level, comprehension of the survey instruments, and voluntary participation. Structural Equation Modelling (SEM) was applied to simultaneously test measurement and structural models, including gender moderation effects. The findings demonstrate that spiritual value integration exerts a positive and significant impact on learning motivation, while gender functions as a significant moderator, indicating that the strength of influence differs between male and female students. The study concludes that spiritual values can be operationalized as measurable predictors of motivation. Its scientific contribution lies in advancing psych pedagogical understanding, refining causal models in Islamic education, and providing evidence-based insights for inclusive, gender-sensitive pedagogical practices.